2021
DOI: 10.3390/su132111692
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mechanical Properties of Cement-Stabilized Soft Clay Using Garnet Residues and Tire-Derived Aggregates for Subgrade Applications

Abstract: The growth of the global economy in recent years has resulted in an increase in infrastructure projects worldwide and consequently, this has led to an increase in the quantity of waste generated. Two recycled materials, namely garnet residues (GR) and tire-derived aggregates (TDA), were used to improve mechanical properties of soft clay (SC) subgrade in this study. GR was evaluated as a replacement material in SC prior to Type I Portland cement stabilization. TDA was also studied as an elastic material in ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A similar study was performed on clay soils, and the results showed an improvement in the permeability and resistance behaviour of poor clay soils [102,103]. In addition, there have been several recent studies exploring the use of raw GTR mixtures [104] and the use of cement-GTR [105] or mortar-GTR mixtures [106] in expansive clay soils. These studies have shown significant improvements in the geotechnical properties and stability of expansive clay soils, one of the major problems in building foundations.…”
Section: General Civil and Building Construction Usesmentioning
confidence: 78%
“…A similar study was performed on clay soils, and the results showed an improvement in the permeability and resistance behaviour of poor clay soils [102,103]. In addition, there have been several recent studies exploring the use of raw GTR mixtures [104] and the use of cement-GTR [105] or mortar-GTR mixtures [106] in expansive clay soils. These studies have shown significant improvements in the geotechnical properties and stability of expansive clay soils, one of the major problems in building foundations.…”
Section: General Civil and Building Construction Usesmentioning
confidence: 78%
“…Due to the low adhesion property of TDA, unconfined compressive strength and stiffness of cementstabilized SC-GR reduce with the increase in TDA content. The cement-TDA-stabilized SC-GR at SC:GR of 90:10, cement content of 2% and TDA content of 2% is suggested by [7] as a sustainable subgrade material.…”
Section: Highlights Of the Contributionsmentioning
confidence: 99%
“…Several papers proposed sustainable ground improvement techniques [1][2][3][4][5][6][7] and soil reinforcement with alternative materials such as recycled polypropylene fibers [8], recycled tire-derived aggregates [9], recycled polyethylene terephthalate strips [10] or polypropylene waste strips [11].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in order to investigate the influence law of confining pressure on the cyclic and post-cyclic behavior in more detail, the maximum confining pressure is 300 kPa. Sukmak [44] and Ho [45] conducted a series of laboratory tests to analyze the engineering performance of stabilized soft soil and suggested that the range of cement content was 5-15%. In order to investigate the influence of cement content on cyclic and post-cyclic behavior in more detail, the cement contents range from 3% to 15%.…”
Section: Test Procedures and Experimental Schemementioning
confidence: 99%